First record of Naushonia sp. (Decapoda: Laomediidae) larva from the Equatorial Atlantic - de Albuquerque Lira, Simone Maria; de Santana, Claudeilton Severino; Schwamborn, Ralf (Zootaxa, 2018)
The first zoeal-stage larva of a possibly new species of mud shrimp Naushonia (Decapoda: Gebiidea: Laomediidae) was described from plankton samples taken off the Fernando de Noronha Archipelago, being the first occurrence at the oceanic islands of the Equatorial Atlantic. Five zoea I larvae were obtained and dissected for observation of mouthparts. This zoea I of Naushonia sp. is well distinguished from the first larvae of N. portoricensis (Rathbun 1901) from the Caribbean and N. cangronoides (Kingsley 1897) from the Northwest Atlantic in terms of development and setation of appendages, and possibly belongs to a new, undescribed species. The present study widens the knowledge on tropical oceanic decapod larvae and provides detailed drawings and new photographic illustrations with extended depth of field of these organisms.